Au NCs-enhanced chemiluminescence from NaHSO3–H2O2 and its analytical application. Issue 6 (11th January 2016) - He, Yanyan; Sui, Yanyan; Xu, Shuangjiao; Chen, Funan
Abstract : It was found that the ultra-weak chemiluminescence (CL) emission from the sodium bisulfite (NaHSO3 )–H2 O2 system could be enhanced by gold nanoclusters (Au NCs). Abstract : It was found that the ultra-weak chemiluminescence (CL) emission from the sodium bisulfite (NaHSO3 )–H2 O2 system could be enhanced by gold nanoclusters (Au NCs). The as-prepared Au NCs were applied to the NaHSO3 –H2 O2 system for the first time, and a decreased CL was observed in the presence of trypsin. This novel CL system based on Au NCs–NaHSO3 –H2 O2 was developed for trypsin determination. Herein, UV-visible spectroscopy and fluorescence spectra coupled with radical scavengers were used to explore the possible mechanism. The enhanced CL could be attributed to the catalysis of Au NCs and the decreased CL should be ascribed to the decomposition of Au NCs. Finally, the proposed method was successfully utilized to detect trypsin in human urine samples with good accuracy and precision.